Mother personality trait and maternal role adaptation of first-time mothers: Self differentiation as a mediator - Muthi'ah, Adisty Ghaisani; Halim, Magdalena S. (Faculty of Psychology, Universitas Diponegoro, 2024)
Background: Mothers, especially first-time mothers, are expected by society to suitably adapt to their new role so they can nurture their children properly. Mother's self-differentiation examines their capacity to discern themselves to others and how it will help them adapt better in their transition. In this research, self-differentiation acts as a mediator between mothers' personality and their capability in maintaining their new role as a mother. Purpose: This research analyzes the mediation role of self-differentiation between personality and abilities of first-time mothers regarding their adaptation to their new role.Method: 107 participants, aged between 21 and 25 years, who have children under one year old, and an average marriage age of 1-3 years. Three measuring instruments were used, the International Personality Item Pool-Big Five Markers 50 (IPIP-BFM-50), the Differentiation of Self Scale in Two Domains (DSS-2D), and the Maternal Role Adaptation Questionnaire (MRAQ).Findings: Results indicate that aspects of mothers’ personality influence their maternal role adaptation. Furthermore, aspects of self-differentiation, significantly mediate the relationship between the mother's personality and maternal role adaptation.Implication: Mothers’ self-differentiation will support their adaption in her new role as a mother. Therefore, interventions in helping first time mothers could involve mothers' self-differentiation and personality aspects